Students on strike: struggle, resistance, and subjectivation (Praxis Educativa, 2024)
This paper analyzes the experiences of participation in the strike carried out by students of Unit 071 of the National Pedagogical University of Tuxtla Gutierrez, Chiapas, Mexico. From a reflective approach, the historical memory of the process is recovered from documentary analysis, records of assemblies and marches, as well interviews with students and leaders of the movement. The information was grouped into two blocks: From the pandemic to the student strike. Subjectivation and existential plot; in which the vicissitudes of organization and actions carried out are exposed; and, The word must be worth, which discusses the network of actions, synergies, meetings and disagreements between students to undertake negotiations with educational and governmental authorities. The confluence of other social movements, the mobilization and taking of the streets, contributed to the strike's resolution, which inaugurated an unprecedented experience of struggle and resistance for these students.
Keywords: student movements, university, education.